Độ vững mạnh của nền tảng kinh tế vĩ mô tại Việt Nam - Lý Đại , Hùng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This paper investigates the soundness of macroeconomic fundamentals in Vietnam, by a time-varying coefficients bayesian structural vector autoregression (TVC-BSVAR) model over a quarterly sample over Q1/2007–Q4/2020 period. The evidence records three macroeconomic principles: The trade-off between output and inflation, VND depreciation rate enhancing output growth rate, and lower inflation improving economic growth. The macroeconomic structure determines the macroeconomic resilience to world economy shocks. Especially, the disbursed FDI capital can substitute the world GDP growth rate on raising domestic GDP growth rate, inflation rate; and evaluating domestic currency. Based on a close linkage of macroeconomic variables combined with considerable impact induced by external shocks from the world economy, the paper uncovers that the soundness of macroeconomic fundamentals in Vietnam is quite strong and also suggests that the improvement of FDI absorption capacity needs to be a prioritised policy for the economy to have additional policy residency to self-insure against the negative shocks from world GDP growth rate and oil price.
Keywords: Macroeconomic fundamentals; Vector autoregression; External shocks